Genetic similarity in a hybrid population of ’Montenegrina’ and ’King’ mandarins - Brugnara, Eduardo Cesar; Bastianel, Marinês; Weiler, Roberto Luis; Schwarz, Sergio Francisco (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to confirm the hybrids obtained in plants originated from the crossing between the mandarins Citrus deliciosa 'Montenegrina' and C. nobilis 'King', and to estimate the genetic similarity among hybrids, and between each hybrid and its parents. Twenty‑three pairs of microsatellite primers were tested. Fourteen of these pairs showed polymorphic bands between parents. Primers CCSM 129 and CCSME 52 were sufficient to identify the 12 nucellar clones observed in the studied population. Genetic similarity analysis of the population (hybrids and parents) showed 0.56 average similarity. Besides the 12 clones of 'Montenegrina' identified, 25 hybrids were found of which D18, C32, D06, C05 and D09 are the more similar to 'Montenegrina'.